Regionalização dos parâmetros de um modelo chuva-vazão para estimativa de vazões em bacias sem monitoramento sistemático - Vendruscolo, Janice (2005)
This research had as an objective to verify the usage aplicability of the regionalization of the parameters about rain flow model, in order to synthesize flows at poorly places on hydrometereologicals data. The methodology had three phases: data acquisition, model adjusting and hydrologic regionalization. The adjust model chosen was the rain-flow hydrologic model MOPH, developed by Silveira (1974). This model has a simple structure, that works with precipitation datas and potential evapoperspiration rates, also it has an algorithm of the escapement separation and of the propagation about them. The model has nine parameters: SMAX, UMIDL, UMIDS, CODIS, DISTR, EXPO, Ktanque, KSUB and KSUP. The model parameters regionalization process used five explanation variables: drainage area (A), principal river length (L), principal river declivity (D), drainage density (DD) and compacity coefficient (CC). The results demonstrated that UMIDL, UMIDS, CODIS and Ktanque parameters had a few sensibility on the adjusts, on this way these parameters was considered constant for all region of this study. The others parameters showed promising results when they formed continual regions hydrologicaly homogeneous.